Comparative evaluation of immediately loaded implants in both immediate and delayed implant placement with cone-beam computed tomography analysis - Vedhavani Muthaiyan; Malathi Krishnamurthi; Muthukumaraswamy Arunachalam; Shabbir Ahamed Mujeeb; Chagnoor Hima Bindu Reddy (Journal of Indian Society of Periodontology)
Background: Conventionally, dental implants were placed several months after tooth extraction. Immediate implants were placed on the same day of extraction along with the conservation of the crestal bone. Immediate loading of implant facilitates immediate prosthetic reconstruction within 48 h of implant placement. In this study, both immediate and delayed implants were loaded immediately and their peri-implant bone loss, implant stability, and the soft-tissue outcomes around the implant were evaluated. Materials and Methods: Fourteen patients were included in this study, of which seven patients were under Group A (delayed) and seven patients were under Group B (immediate). The clinical evaluation was done at baseline, 3 months, and 6 months which includes plaque scores, bleeding on probing, and probing depth. Implant stability was tested by resonance frequency analyzer (implant stability quotient), and radiological evaluation of crestal bone loss was done by cone-beam computed tomography preoperatively and after 6 months. Results: In this study, there was no statistically significant difference (P > 0.05) in the clinical parameters (plaque index, bleeding on probing, and probing depth) and radiological outcomes within the groups at baseline, 3 months, and 6 months. The implant stability quotient and crestal bone loss between Groups A and B showed a statistically significant difference at baseline and 6 months, wherein there were higher implant stability and decreased crestal bone loss in Group A when compared to Group B. Conclusion: Delayed implants with immediate loading were superior to immediate implants with immediate loading.